PREVALENCE OF MONIEZIOSIS IN SHEEP - Safarov Kh. A.; Akramov K. Sh. (Web of Journals Publishing, 2025)
This article presents an analysis of data on the prevalence of monieziosis in sheep across various regions and the types of the disease observed.
Keywords: Sheep, helminth, helminthosis, Moniezia, Moniezia benedeni, Moniezia expansa.